The Relationship Between Retention Factors and Career Commitment - Nur Damayanti (2009)
The main objective of this study is to examine the relationship between retention factors and career commitment. The five factors that measured retention were compensation,training and development, job characteristic, supervisor support and promotion.Data were gathered through questionnaire survey of employee at ACM Sdn. Bhd. (n=253). Correlation and regression analysis were used of examine the relationship between retention factors and career commitment. The results indicated that compensation, training and development, job characteristic, supervisor support and promotion were positively correlated with career commitment. The multiple regression results suggest that compensation were the most important factors in influencing career commitment. The findings were discussed and recommendations for further research were also addressed.